Endo-β-1,3-galactanase from Winter Mushroom Flammulina velutipes - Kotake, Toshihisa (American Society for Biochemistry and Molecular Biology, 2011)
Arabinogalactan proteins are proteoglycans found on the cell surface and in the cell walls of higher plants. The carbohydrate moieties of most arabinogalactan proteins are composed of β-1,3-galactan main chains and β-1,6-galactan side chains, to which other auxiliary sugars are attached. For the present study, an endo-β-1,3-galactanase, designated FvEn3GAL, was first purified and cloned from winter mushroom Flammulina velutipes. The enzyme specifically hydrolyzed β-1,3-galactan, but did not act on β-1,3-glucan, β-1,3:1,4-glucan, xyloglucan, and agarose. It released various β-1,3-galactooligosaccharides together with Gal from β-1,3-galactohexaose in the early phase of the reaction, demonstrating that it acts on β-1,3-galactan in an endo-fashion. Phylogenetic analysis revealed that FvEn3GAL is member of a novel subgroup distinct from known glycoside hydrolases such as endo-β-1,3-glucanase and endo-β-1,3:1,4-glucanase in glycoside hydrolase family 16. Point mutations replacing the putative catalytic Glu residues conserved for enzymes in this family with Asp abolished activity. These results indicate that FvEn3GAL is a highly specific glycoside hydrolase 16 endo-β-1,3-galactanase.